O impacto do uso de dispositivos digitais nas escolas públicas como ferramenta de ensino - Nagy, Marcio José Santos (2014)
This research conducts a study on the impact of the use of digital devices such as teaching tool, particularly of tablets in the public schools, allowing ownership of processes, concepts and logics own digital technology by teachers. For this, the research has as one of its objectives to understand how governmental strategies for the use of digital content, may contribute to the teaching practice. The study also examined the infrastructure and geographic reach of schools, teachers and current competence of the results achieved in private schools in Brazil and other countries. Understand why investments in technology in education has not reached the expected benefits is the first step towards the implementation of new strategies and avoid repeating mistakes in getting better results. To achieve this objective analysis that can answer questions will be held: For what to use technology? How to transform the way you teach with this feature? The relationship between teacher and student should be changed? Teacher training must undergo changes, as well as the culture of the school? From the literature review and document analysis, academic texts related to the topic and experiences in Brazil and abroad, we could realize a greater focus on hitting strategies for use of digital resources in the country. However, because of the deficiencies of the technological quality of government policies and the training of teachers, we still have a long way to have traveled to get results in the improvement of education through the use of these resources. The conclusion of the dissertation emphasizes that we must not neglect all relevant aspects of the role of teacher to the appropriate use of technology resources in public schools, so that the technology can also be a major pillar in the improvement of education in Brazil